PERAN AUDIT INTERNAL GUNA MENINGKATKAN KINERJA (STUDI KASUS DI PT BPR ARMINDO KENCANA MALANG) - Lucia Oktaviana (Ma Chung Press, 2015)
The purpose of this study is to analyze the role of internal audit in improving performance of PT BPR Armindo Kencana Malang. The research data was obtained from a questionnaire distributed to 34 respondents and interview results is an opinion expressed by heads of sections. The questionnaires were analyzed by using champion method. The results showed that the percentage value of the three questionnaires are 67%, 66%, 65%, which means that internal audit has sufficient role in improving the effectiveness, efficiency, and economy of obedience performance, financial performance and managerial performance. In some item of questionnaires, respondents said that internal auditors are quite intensive in doing monitoring, but also in some item of questionnaires, internal auditor are still less intensive in doing monitoring. So, this study can be concluded that internal auditors have sufficient role on giving contribution to the performance, but in the future internal auditors must have a role more intensive in order to maximize the contribution made.